A "validade" da "arte paranaense" na crítica de Adalice Araújo - Oliveira, Luana Hauptman Cardoso de (Revista do Colóquio, 2020)
Adalice Araújo (1931 - 2012) was the main art critic of Paraná. During her career, one of her main concerns was that art and artists from Paraná would be understood as part of a national art system and not classified as regional. To achieve this goal Adalice acted on several fronts, but it was as an art critic linked to the newspapers in Curitiba that her ideas had the greatest repercussion. Thus, in view of what Roland Barthes called "validities", this article aims to analyze the meaning of the use of the term "arte paranaense" by Adalice Araújo. The hypothesis is that when referring to the art of Paraná in a key that leads to “regionalist” interpretations and at the same time bringing the production of these artists closer to discussions about avant-garde and “Geração 80”, Adalice Araújo creates a resource to highlight what , although supported by national discussions, it was specific to the Paraná field, without, however, defending any type of regionalism.